2022
DOI: 10.1002/smll.202201352
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Point Defects Endows n‐Type Bi2Te3 with High Thermoelectric Performance and Superior Mechanical Robustness for Power Generation Application

Abstract: Bi2Te3‐related alloys dominate the commercial thermoelectric market, but the layered crystal structure leads to the dissociation and intrinsic brittle fracture, especially for single crystals that may worsen the practical efficiency. In this work, point defect configuration by S/Te/I defects engineering is engaged to boost thermoelectric and mechanical properties of n‐type Bi2Te3 alloy, which, coupled with p‐type BiSbTe, shows a competitive conversion efficiency for the fabricated module. First, as S alloying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 56 publications
0
29
1
Order By: Relevance
“…Lattice parameter c exhibited obvious expansion compared with the lattice parameters a and b . [ 31 ] It is well known that Bi 2 Te 3 consists of the quintuple‐layer unit ‐Te(1)‐Bi‐Te(2)‐Bi‐Te(1)‐, which interconnects by van der Waals forces. As explored by Hashibon et al., [ 32 ] the antisite defects Bi′ Te in Bi 2 Te 3 are more inclined to be generated at Te(1) sites.…”
Section: Resultsmentioning
confidence: 99%
“…Lattice parameter c exhibited obvious expansion compared with the lattice parameters a and b . [ 31 ] It is well known that Bi 2 Te 3 consists of the quintuple‐layer unit ‐Te(1)‐Bi‐Te(2)‐Bi‐Te(1)‐, which interconnects by van der Waals forces. As explored by Hashibon et al., [ 32 ] the antisite defects Bi′ Te in Bi 2 Te 3 are more inclined to be generated at Te(1) sites.…”
Section: Resultsmentioning
confidence: 99%
“…crystal defects. [63] For example, Zhu et al [22] found that creating point defects by adding indium to a Bi 2 Te 3 alloy increased the zT by more than 10 times that of pristine Bi 2 Te 3 . Alloying Bi 2 Te 3 with sulfur increased the zT from 0.1 to 0.7, owing to an increased Seebeck coefficient, electrical conductivity and reduced thermal conductivity by the sulfur atoms reducing antisite defects.…”
Section: Telluridesmentioning
confidence: 99%
“…Thermoelectric (TE) materials have been intensely considered for cooling and power generation applications due to the ability to convert heat and electricity into each other. [1][2][3][4] The thermoelectric efficiency of a TE material can be measured by the thermoelectric figure of merit 5 zT = S 2 sT/k, where S is the Seebeck coefficient, s is the electrical conductivity, T is the absolute temperature, and k is the total thermal conductivity including phononic (k l ) and electronic (k e ) thermal conductivity, respectively. Apparently, increasing the power factor (PF = S 2 s) by tuning the band structure and/or reducing k by increasing phonon scattering are straightforward to enhance zT values.…”
Section: Introductionmentioning
confidence: 99%